The Not Accepted Neighbour. The African Immigrant’s Residential Situation in Almería (Spain) - (:unkn) unknown (My University, 2005)
In this article the residential situation of the immigrants coming from Africa to the province of Almería is described, analyzing mainly two aspects. Firstly, the residential segregation starting from the indexes of dissimilarity, isolation and absolute centralization. Secondly, the characteristics of the lodgings inhabited by the immigrants, taking as reference the indicators of stability, adaptation, habitability and residential accessibility. The data are obtained from the Municipal Census and a survey. The results show a high residential segregation and a deficient residential situation, where almost three out of every four African immigrants live in a residence not deign. The main reason that explains this situation is the ethnic discrimination.
Keywords: African Research